Comment on "Conservation Laws of Two (2 + 1)-Dimensional Nonlinear Evolution Equations with Higher-Order Mixed Derivatives". (28th January 2014) - Wei, Long; Wang, Yang
Abstract : In a recent paper (Zhang (2013)), the author claims that he has proposed two rules to modify Ibragimov's theorem on conservation laws to "ensure the theorem can be applied to nonlinear evolution equations with any mixed derivatives." In this letter, we analysis the paper. Indeed, the so-called "modification rules" are needless and the theorem of Ibragimov can be applied to construct conservation laws directly for nonlinear equations with any mixed derivatives as long as the formal Lagrangian is rewritten in symmetric form. Moreover, the conservation laws obtained by the so-called "modification rules" in the paper under discussion are equivalent to the one obtained by Ibragimov's theorem.